Die Gründungsdynamik in technologieorientierten Industrien: Eine Analyse der IAB-Beschäftigtenstatistik - Eric A. Nerlinger (Zentrum für Europäische Wirtschaftsforschung (ZEW); ZBW – Leibniz Information Centre for Economics, 1995)
During the last years more and more discussions came up about the contribution of technology-oriented and technology-intensive industries for the economic development and employment. One reason for these contradictory evaluations of technology-intensive industries can be attributed to different conceptual definitions of technology which are briefly discussed. The foundation and liquidation dynamic of West-Germany is examined for the period 1979-1992 on the basis of a data set from the employment statistics of the Federal Institute of Labour and the Institut für Arbeitsmarkt- und Berufsforschung (lAB). The result is that there are great differences in the foundation and liquidation performance between technology-oriented, not technology-intensive and selected parts of the service sector. The effect of the economic development is analysed in the final part of the paper, showing that technology-oriented industries are more linked to the economic performance than other industries.
Keywords: 330; Unternehmensentwicklung; Unternehmensgründung; Technologie; Konkurs; Arbeitsmarkt; Deutschland